Respuesta :

Here use the quadratic formula
Ver imagen ariannacxu

Answer:

x = 2 + √10

    -------------

           3

x =  2 - √10

     ------------

            3

Step-by-step explanation:

3x² - 3x - 1 = x + 1

         -x - 1  -x  -  1

3x² - 4x - 2 = 0

-b +/- √b² - 4ac              -(-4) +/- √(-4)² - 4(3)(-2)         4 +/- √16 + 24

         ------------------    =            ----------------             =   -----------------

               2a                                 2(3)                                  6

4+/-√40        4 + √ 4 × 10         4 +2√10         2 + √10

------------  =      -------------     =     ------------    =   ------------

     6                       6                        6                  3

                     4 - √ 4 × 10           4 - 2√ 10           2 - √10

                      ----------------    =   -----------------   =    ---------------

                               6                         6                        3

I hope this helps!